Ligeti’s Sonic Odyssey. Music as a Gateway to the Unknown in 2001: A Space Odyssey - KOPEĆ, Martyna (Studia Universitatis Babes-Bolyai Musica, 2024)
Music in Stanley Kubrick’s 1968 film 2001: A Space Odyssey plays a crucial role in eliciting moods due to its sparse dialogue. Instead of using typical film score, Kubrick decided to use already existing recordings of four classical music composers. György Ligeti’s compositions stand out in a stark contrast to the overall soundtrack of the film and evoke a sense of eeriness. Film's plot unfolds through four segments, each marked by an appearance of a monolith, with Ligeti's music acting as a leitmotif. Micropolyphonic textures, characterized by dense musical layering and dissonance, reflect hidden and inaudible aspects of the unknown, comparable to the vastness of outer space.